ANALISIS KINERJA KEUANGAN PADA PT PESONA PERMAI FLORES-NTT - Irmina Paulina Nende Day (LPPM Universitas Bina Bangsa, 2023)
The purpose of this study was to observe and analyze how the financial performance of PT. PESONA PERMAI FLORES-NTT by analyzing activity and profitability indicators. The survey method is a survey that conducts online interviews with executives and company employees by telephone, and a survey that uses literature and writings that are closely related to the subject of writing, with the aim of obtaining the underlying theory. To discuss the problem under investigation. The results showed an increase in activity indicators, including receivables turnover, inventory turnover, and total asset turnover, although there was a slight decrease in total asset turnover from 0.11 to 1,90 in 2021. There was an increase. On the other hand, the rate of return which includes gross profit margin, net profit margin, and rate of return on investment increased from 2019 to 2021